2013
DOI: 10.1038/emboj.2013.183
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor-mediated IRE1α activation as a therapeutic target for inflammatory arthritis

Abstract: In rheumatoid arthritis (RA), macrophage is one of the major sources of inflammatory mediators. Macrophages produce inflammatory cytokines through toll‐like receptor (TLR)‐mediated signalling during RA. Herein, we studied macrophages from the synovial fluid of RA patients and observed a significant increase in activation of inositol‐requiring enzyme 1α (IRE1α), a primary unfolded protein response (UPR) transducer. Myeloid‐specific deletion of the IRE1α gene protected mice from inflammatory arthritis, and treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
177
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 178 publications
(190 citation statements)
references
References 81 publications
12
177
1
Order By: Relevance
“…4C). Analogous experiments using 4μ8c in the same animal model [using previously published doses that showed no toxicity (33,37,40,48)] produced similar results (Fig. 4 D-F): 4μ8c treatment led to a significant reduction (45.2%; P < 0.001) in atherosclerotic lesion area in en face aorta preparations (Fig.…”
Section: Resultssupporting
confidence: 65%
See 3 more Smart Citations
“…4C). Analogous experiments using 4μ8c in the same animal model [using previously published doses that showed no toxicity (33,37,40,48)] produced similar results (Fig. 4 D-F): 4μ8c treatment led to a significant reduction (45.2%; P < 0.001) in atherosclerotic lesion area in en face aorta preparations (Fig.…”
Section: Resultssupporting
confidence: 65%
“…Consistent with these observations, treatment with IRE1 inhibitors led to a marked suppression of hyperlipidemia-induced Th-1 immune responses in these mice. We observed no differences in T-cell numbers in adventia/lesions between the IRE1 inhibitor treatment and control groups, and previous studies have shown the IRE1 inhibitor used in this study does not affect Treg cells (33,37). Collectively, these findings show that prevention of inflammasome-associated cytokine production by IRE1 inhibitors in vivo has dramatic effects on counteracting atherosclerotic disease progression.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…There have been a number of interesting connections identified in RA between aberrant UPR and increased inflammatory responses. As in TRAPS, synovial macrophages, synovial fibroblasts and PBMCs from RA patients were found to have increased Xbp-1 splicing but not increased expression of classical UPR response genes, leading to increased production of pro-inflammatory cytokines, IL-6 and TNF [74,75]. Endogenous TLR ligands which have been found in the joint, such as SNAPIN, may act to induce this aberrant Xbp-1 splicing and sustain inflammatory responses [76].…”
Section: Protein Misfolding and Proteotoxic Stress In Non-mendelian Imentioning
confidence: 93%